Natural Vs. Supernatural Elements in W. B. Yeats's The Only Jealousy of Emer (مجلة ديالى للبحوث الانسانية, 2023)
AbstractThe Only Jealousy of Emer (1917-1918) is a dance play composed by W. B. Yeats of a very beautiful verse which is unmatched ever since. The play comes within Yeats's collection of the so-called Cuchulain Plays. It tells about the tragic fate of the mythical hero, Cuchulain, in his struggle against natural and supernatural elements alike.Soon, both his wife, Emer, and his mistress, Eithne Inguba are engaged in similar combat against supernatural elements to regain Cuchulain alive after being captivated by the so-called Sidhe or fairy people. However, apart from mythical elements, the playwright enhances his portrayal of female characters comprising wife, mistress, and supernatural woman with a touch of realism. Thus, by bringing the hero safely into the world of the living, through Emer's sacrifice, Yeats shows the triumph of human passion and marital duties over the supernatural quest to mate with mortals represented by Fand.Furthermore, the three women alluded to recurred the most influential women characters in Yeats's life; Georgie Hyde Lees, Maud Gonne, and her seventeen-years-old daughter, Iseult. The significance of this reference will be discussed throughout the paper. Therefore, the aim of this paper is to show how natural and supernatural elements function to bring about the tragic fate of the hero, Cuchulain, and how both his wife and mistress are seen combating against supernatural elements.It turns out that the "amorous" (Yeats, 283) Cuchulain who took much delight in having multiple love affairs with women had also relationships with fairies. It was his amorous connection with the supernatural Aoife which brought about his tragic fate in The Only Jealousy of Emer. Cuchulain had a son by Aoife, whom he had unknowingly killed in On Baile's Strand. On knowing that it was his own son, the outraged Cuchulain turned to fight the sea. It was such a ruthless battle that other kings while attending the scene were "like cattle in a gale" (284).